PENGARUH KECERDASAN EMOSIONAL, KECERDASAN INTELEKTUAL DAN MINAT BELAJAR TERHADAP TINGKAT PEMAHAMAN AKUNTANSI PADA MAHASISWA TINGKAT AKHIR JURUSAN AKUNTANSI: Emotional Intelligence; Intellectual Intelligence; Learning Interest; Accounting Comprehension - MARTUA YEHEZKIEL LUMBAN TOBING, RIDHO; Azmiana, Risca (SCIENTIA JOURNAL, 2024)
This  study  looks  at  how  emotional  intelligence,  intellectual  intelligence,  and  learning  interest  affect  accounting  understanding  at  Universitas  Riau  Kepulauan,  Universitas  Internasional  Batam,  Universitas  Ibnu  Sina,  Universitas  Batam,  and  Universitas  Universal.  The  research  population  consists  of  1,475  students,  and  data  was  collected  through  an  online  survey  using  Google  Forms.  A  total  of  165  respondents  were  selected  using  purposive  sampling  with  the  Slovin  formula.  The  questionnaire  questions  were  evaluated  with  a  Likert  scale,  and  the  data  was  analyzed  using  IBM  SPSS  Version  25.  The  study  includes  descriptive  statistics,  validity-reliability  tests,  classical  assumptions,  multiple  linear  regression,  and  both  partial  and  simultaneous  hypothesis  testing.  The  results  show  that  emotional  intelligence  mostly  doesn’t  have  a  significant  effect  on  accounting  understanding,  while  intellectual  intelligence  and  learning  interest  do  have  a  significant  partial  effect  on  accounting  understanding.  Overall,  all  three  factors  collectively  affect  accounting  understanding.  The  Adjusted  R  Squared  value  of  28.6%  indicates  that  emotional  intelligence,  intellectual  intelligence,  and  learning  interest  influence  accounting  understanding